2012
DOI: 10.4103/2156-7514.97755
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Study of the Prevalence of Dens Invaginatus in a Sample Set of Turkish Dental Patients

Abstract: Aim:The aim of this study was to determine the prevalence of dens invaginatus in a sample of Turkish dental patients.Materials and Methods:The sample included 6, 912 panoramic radiographs from different Turkish dental patients. The ages of the patients ranged from 18 to 50 years. A tooth was considered having dens invaginatus if an infolding of a radiopaque ribbon-like structure equal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
1
16
0
5
Order By: Relevance
“…Bilateral cases of dens in dente are also not uncommon, the bilateral incidence with symmetrical distribution was 25% in the study by Çolak et al, 27 and an evaluation performed Shi et al 30 found that the bilateral occurrence was 19.05% of cases with dens in dente.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bilateral cases of dens in dente are also not uncommon, the bilateral incidence with symmetrical distribution was 25% in the study by Çolak et al, 27 and an evaluation performed Shi et al 30 found that the bilateral occurrence was 19.05% of cases with dens in dente.…”
Section: Discussionmentioning
confidence: 94%
“…According to Çolak et al, 27 the different types of dens in dente may be related to several factors, including differences in the study sample, geographical locations, gender differences, and chronological age. In a study with a Turkish population, it was observed that this malformation reached 0.17% of individuals, detected in 15 out of 192,150 teeth, with a prevalence of 0.008, occurring in 12 MLIs and 3 maxillary canines.…”
Section: Discussionmentioning
confidence: 99%
“…Dens in dente olarak da bilinen dens invajinatus, diş dokularının kalsifikasyonundan önce, mine organının dental papilla içerisine uzanmasıyla oluşan, tek taraflı veya simetrik gözlenebilen gelişimsel bir malformasyondur. 1 Literatürde, prevalansının %0.04-12 arasında olduğu [1][2][3][4][5][6][7][8] , en sık daimi üst lateral dişlerin dens invajinatustan etkilendiği bildirilmiştir. [4][5][6]8,9 Etyolojisi tam bilinmemekle birlikte, diş germine çevre dokulardan gelen anormal basınçlar, iç mine epitelinin lokalize gelişim yetersizliği, travma, enfeksi -yon gibi hem çevresel hem genetik faktörleri içerdiği bildirilmiştir.…”
Section: Gġrġġunclassified
“…They most commonly occur at the bifurcation or trifurcation of molars and are rare on incisor teeth. The incidence of enamel pearls in humans is approximately 5% ( 76 , 77 ), but its occurrence in dogs is uncertain and should be investigated ( 78 ). Microscopically, the enamel pearl consists of a core of dentin covered by enamel and may contain a pulp chamber continuous with the larger pup chamber of the tooth.…”
Section: Odontogenesismentioning
confidence: 99%